An experimental analysis of jackpot reinforcers. Issue 3 (1st April 2020) - Kuroda, Toshikazu; Roca, Alicia; Hall, Ezra G.; Jarmolowicz, David P.; Lattal, Kennon A.
Abstract : Animal trainers and others often recommend the use of jackpot reinforcers, which are disproportionally large and come as a "surprise" to the animals. Because the actual behavioral effects of these jackpots remain uninvestigated, many basic questions about their use and even definition are unanswered. This series of experiments explored the definitions of jackpots using several different behavioral tests with both rats and pigeons. Because the original description of a jackpot resembled the reinstatement of previously reinforced and extinguished responding with response‐independent deliveries of reinforcer, reinstatement effects of a jackpot, defined by its quality, were examined with rats in Experiment 1. In Experiment 2, response‐potentiating effects of response‐independent and ‐dependent deliveries of a jackpot, defined by its quantity, were assessed with pigeons when responding had nearly ceased. The response‐potentiating effects of the frequency of jackpot‐reinforcer delivery were investigated when responding of pigeons was maintained in single (Experiment 3) or concurrent (Experiment 4) schedules of reinforcement. Effects of jackpots on resistance to change were assessed with rats in Experiment 5. The effects of jackpots in each experiment were either absent or unsystematic across the subjects, casting doubt on their utility in animal training. Possible factors contributing to the negative results are discussed.